THERAPEUTIC INVESTIGATION OF PALM DATE (PHOENIX DACTYLIFERA) SEED POWDER SUPPLEMENTATION ON GLYCEMIC BIOMARKERS OF WOMEN WITH HIGH BLOOD GLUCOSE LEVEL: A RANDOMIZED CONTROLLED TRIAL - Hüseyin Şahin; Mehmet Burak Peköz; Efe Mehmet Can Kırca; Kashif Riaz; Asma Batool (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Diabetes is a long-term metabolic illness characterized by impaired insulin secretion or sensitivity along with poor glucose management. Diabetes has several systemic effects, including microvascular (retinopathy, nephropathy, and neuropathy) and macrovascular (ischemic heart disease, stroke, and peripheral vascular disease) outcomes. Asian groups experience diabetes at a younger age than do white cultures, which means that young Asians are more likely to experience the morbidity and mortality associated with the disease as well as its implications. Pathogenetic variables for diabetes and its thresholds in Asian populations exhibit several notable characteristics. Diabetes has a significant financial cost to individuals, communities, and the country. The presence of antioxidant polyphenols in date palm fruits makes them one of the most promising fruits when it comes to treating diabetes. The goal of current research is to investigate the anti-diabetic effects of palm date seed powder. For this purpose and date palm fruit supplementation powder were analyzed firstly for its chemical composition along with its phenolic profile. Afterwards the antidiabetic properties were checked on human subjects. Results showed that it has contains moisture, ash content, crude fat, crude protein, crude fiber, and nitrogen free extract (NFE) 4.76 ± 0.34, 5.89 ± 0.17, 6.45 ± 0.27, 1.48 ± 0.24, 9.89 ± 0.57 and 62.85 ± 10.54 mg /dl, respectively and TFC and TPC in term of phenolic content were observed as 42.45 mg CE/g db and 154.48 mg GAE/g db. In addition, the hyperglycemic biomarker was indicated in the treatment groups that had already been planned by administering the therapeutic supplemented powder in the form of capsules. Over the course of 60 days, the experimental groups (T1 and T2) received supplemental powder of date palm (4 g for T1 group and 8 g for T2 group, respectively. For two months, the effects of date palm seed powder supplementation on the blood sugar levels of diabetic patients were monitored every seven days. The HbA1c test was performed both before and after the two-month clinical experiment. HbA1c and the random blood sugar level were both very significant, according to the ANOVA results.